Farmers to Industry Connector a Modern Approach to Agriculture - A.Bharath simha Reddy, E.K.Subramanian (International Journal of Advanced Science and Technology, 2020)
Although there is no single definition of sustainable agriculture upon which everyone agrees, a general consensus seems to exist for three dimensions of sustainability--environmental, economic and social. Most research on this subject has focused on production factors related to sustainable or organic agricultural practices. However, currently this focus has not matched what producers would agree is their greatest need--a market for what they produce. This proposal addresses the socio-economic dimension of sustainable agriculture by proposing the development of a web-android-based data base management system for the marketing of fruits and vegetables. Not only will the database offer local conventional growers an opportunity to sell directly to Michigan retailers but it will also provide a value-added opportunity for organic and sustainable producers, allowing them to differentiate their produce from conventional producers in the listing of products for sale and earn higher returns. Totally, the focus of the research is to make ease of doing agriculture business on time, with good returns, no wastage and also can attain mutual and desirable transactions